Analysis of the Yield of Radish (Raphanus Sativus L.) Fertilized with Compost Based on Organic Waste from Markets and its Relationship with its Stomatal Density - Cruz Nieto, Dante D. (2022)
For higher yields in vegetable cultivation, the availability of soil nutrients must be improved. Therefore, the aim of this research was to establish the relationship between stomatal density and the yield of the radish crop fertilized with compost made from organic market waste. A completely randomized block design was used, which consisted of 3 blocks and 5 treatments, which were T1, T2, T3, T4 and T5 with 00, 10, 15, 15, 20 and 25 g compost/plant respectively. The physical characteristics of the plants were evaluated from sowing to harvest and the data obtained were processed by analysis of variance and Duncan's test. Chemical analysis of the compost and soil was carried out, as well as a foliar analysis to determine the nutrient concentration by treatment. The results determined that the treatment (T4) stood out in plant length with 28.96 cm, plant weight with 43.33 g, yield of 10.82 t/ha and bulb diameter of 3.92 cm; likewise, in the concentration of nutrients in the leaves, the treatment (T5) highlighted in N with 5.94%, Ca 4.84%, Mg 1.29%, Zn 64.58 ppm and a stomatal density of 642 stomas/mm2. It is concluded that, at an adequate dose of compost, the concentration of nutrients increases, as well as the stomatal density, resulting in higher yields.